Pengaruh POC Teknologi Nano terhadap Pertumbuhan Bayam Merah (Amaranthus tricolor L.) yang Dibudidayakan secara Hidroponik - Afiah, Annisa; Fevria, Resti (Lembaga Yasin AlSys, 2024)
The use of AB mix in hydroponic cultivation has side effects on body health because it is a chemical fertilizer. ). Liquid organic fertilizer is fertilizer in liquid form made from a fermented mixture of compost, natural ingredients and water and can provide nutrients according to plant needs. In hydroponic cultivation there are several weaknesses, including the occurrence of nutrient deposition, especially in the wick system because the nutrient water in the wick system is passive. To reduce the occurrence of nutrient solution deposition in the wick system used in this research, technology is needed that can reduce the particle size in the planting medium so that it is more easily decomposed and absorbed by plant roots. The method used was a completely randomized design (CRD) with 3 treatments and 5 repetitions, consisting of: P1 = AB mix 100%, P3 = AB Mix 50% + POC nano 50%, P5 = POC nano 100%. The data obtained were analyzed using ANOVA (Analysis of Variance) using the SPSS (Statistical package for the Social Sciences) application. If there is a real difference, continue with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results obtained from the influence of POC nanotechnology on the growth of red spinach plants can be seen from the average height of P1 plants, namely 18.74 cm, the average number of leaves 35.2 (strands), wet weight 15.84 g, dry weight 1.4 g. The application of nanotechnology liquid organic fertilizer provides significantly different results on the growth of spinach plants.